Bipolar charge transport in PCPDTBT-PCBM bulk-heterojunctions for photovoltaic applications - Morana, Mauro; Wegscheider, Matthias; Bonanni, Alberta; Kopidakis, Nikos; Shaheen, Sean; Scharber, Markus; Zhu, Zhengguo; Waller, David; Gaudiana, Russell; Brabec, Christoph (Advanced Functional Materials, 2008)
An experimental study of the transport properties of a low-bandgap conjugated polymer giving high photovoltaic quantum efficiencies in the near infrared spectral region (Eg-opt similar to 1.35 eV) is presented. Using a organic thin film transistor geometry, we demonstrate a relatively high in-plane hole mobility, up to 1.5. x 10(-2) cm(2) V-1 s(-1) and quantify the electron mobility at 3 x .10(-5) cm(2) V-1 s(-1) on a SiO2 dielectric. In addition, singular contact behavior results in bipolar quasi-Ohmic injection both from low and high workfunction metals like LiF/Al and An. X-ray investigations revealed a degree of interchain pi-stacking that is probably embedded in a disordered matrix. Disorder also manifests itself in a strong positive field dependence of the hole mobility from the electric field. In blends made with the electron acceptor methanofullerene [6,6]-phenyl C-61 butyric acid methyl ester (PCBM), the transistor characteristics suggest a relatively unfavorable intermixing of the two components for the application to photovoltaic devices. We attribute this to a too fine dispersion of [C60]-PCBM in the polymer matrix, that is also confirmed by the quenching of the photoluminescence signal measured in PCPDTBT [C60]-PCBM films with various composition. We show that a higher degree of phase separation can be induced during the film formation by using 1,8-octanedithiol (ODT), which leads to a more efficient electron percolation in the [C60]-PCBM. In addition, the experimental results, in combination with those of solar cells seem to support the correlation between the blend morphology and charge recombination. We tentatively propose that the drift length, and similarly the electrical fill factor, can be limited by the recombination of holes with electrons trapped on isolated [C60]-PCBM clusters. Ionized and isolated [C60]-PCBM molecules can modify the local electric field in the solar cell by build-up of a space-charge. The results also suggest that further improvements of the fill factor may also be limited by a strong electrical-field dependence of the hole transport.